The Application of The Pogil Model to Improve the Activity and Learning Outcomes of IPA Class V Students UPT SDN Tondrong Saddang - Mohar Mohar; Aminullah Aminullah; Saleha Saleha (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to evaluate the implementation of the POGIL (Process Oriented Guided Inquiry Learning) model in improving the activity and learning outcomes of science students in the fifth grade at UPT SDN Tondrong Saddang. The research employed Classroom Action Research (CAR) with two cycles, each consisting of planning, implementation, observation, and reflection stages. The results indicate a significant improvement in student activity, learning outcomes, and motivation after the application of the POGIL model. In Cycle I, the average student activity was 55%, with formative test results averaging 72.5, and student motivation scoring 3.2. After improvements in Cycle II, all aspects showed growth. Student activity increased to 75%, formative test scores averaged 85.0, and student motivation rose to 4.5. This improvement demonstrates that the POGIL model effectively encourages students to be more engaged in learning, enhances conceptual understanding, and strengthens critical thinking and collaboration skills. Additionally, the POGIL model successfully boosted student motivation, positively contributing to their learning outcomes. This research recommends the application of the POGIL model in science education and other subjects to improve the overall quality of education and further develop students' critical thinking better among students.